1988
DOI: 10.1152/ajpheart.1988.255.3.h646
|View full text |Cite
|
Sign up to set email alerts
|

Increased angiotensin II receptors in brain nuclei of DOCA-salt hypertensive rats

Abstract: We analyzed angiotensin II (ANG II) receptors by in vitro autoradiography in selective brain nuclei of control, salt-treated (1% NaCl in drinking water), deoxycorticosterone acetate (DOCA)-treated (DOCA pivalate, 25 mg/kg sc weekly), and DOCA-salt-treated (DOCA + salt treatments) uninephrectomized male Wistar-Kyoto rats. After 4 wk of treatment, only the DOCA-salt group developed hypertension. ANG II binding increased in median preoptic nucleus and subfornical organ of salt- and DOCA-treated rats. DOCA-treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 0 publications
3
41
0
Order By: Relevance
“…The systemic RAS activity was lower in DOCA-salt rats than in sham-operated rats as indicated by the significantly lower plasma renin activity [0.6 Ϯ 0.1 ng of AngI produced per ml per h, n ϭ 6, vs. 1.7 Ϯ 0.3, n ϭ 6 (P Ͻ 0.05)]. In contrast, the brain RAS was hyperactive in DOCA-salt rats as previously shown by the increased density of AT 1 receptor binding sites observed in the brain of these animals as compared to normotensive WKY rats (33). This hyperactivity could account for the higher pressor response to i.c.v.…”
Section: Effects Of Icv Injections Of Ec33 and Rb150 On Arterial Bmentioning
confidence: 55%
“…The systemic RAS activity was lower in DOCA-salt rats than in sham-operated rats as indicated by the significantly lower plasma renin activity [0.6 Ϯ 0.1 ng of AngI produced per ml per h, n ϭ 6, vs. 1.7 Ϯ 0.3, n ϭ 6 (P Ͻ 0.05)]. In contrast, the brain RAS was hyperactive in DOCA-salt rats as previously shown by the increased density of AT 1 receptor binding sites observed in the brain of these animals as compared to normotensive WKY rats (33). This hyperactivity could account for the higher pressor response to i.c.v.…”
Section: Effects Of Icv Injections Of Ec33 and Rb150 On Arterial Bmentioning
confidence: 55%
“…After DOCA-salt treatment for 1 month, renin-like activity and Ang II in hypothalamus and brain stem nuclei were elevated, but plasma renin activity was very low (7,8). In rats with DOCA-salt hypertension for 4-8 weeks, angiotensin II receptor binding on autoradiography was also elevated in selected brain areas involved in cardiovascular regulation, such as nucleus of solitary tract, area postrema, median preoptic nucleus, subfornical organ, and solitary vagal area (4)(5)(6). Moreover, BP responses to centrally administered Ang II were significant- (4,25).…”
Section: Discussionmentioning
confidence: 98%
“…DOCA-salt-treated rats show higher Ang II receptor density in brain areas involved in cardiovascular regulation, such as the nucleus of solitary tract, area postrema, median preoptic nucleus, subfornical organ, and solitary vagal area (4)(5)(6), and have elevated levels of renin and Ang II in hypothalamus and brain stem nuclei (7,8). Acute intracerebroventricular (icv) administration of captopril decreases the blood pressure of DOCA-salt hypertensive rats (9).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, drinking stimulated by central injection of angiotensin II was increased after DOC administration, demonstrating the behavioral consequences of mineralcorticoid-mediated increases in angiotensin II binding sites (Wilson et al, 1986). Subsequent studies identified increased angiotensin II receptor binding in specific brain regions following DOC administration (De Nicola et al, 1993;Gutkind et al, 1988) as well as within cultured neurons (Sumners & Fregly, 1989). Whether the up-regulation of angiotensin II receptors was due to the actions of mineralcorticoids, glucocorticoids, or a combination of both remained to be determined.…”
Section: Central Interactions Of Aldosterone and Angiotensin IImentioning
confidence: 99%